Enhancing Environmental Sustainability in Vocational Institutions : A Case Study Analysis and Implementation Strategy Certification - Jämsä, Ida (My University, 2024)
The importance of sustainable development and environmental sustainability has in-creased over the years. Global and domestic regulations and carbon neutrality targets also place a responsibility on educational institutions to enhance their environmental sustain-ability. This study aims to establish a framework for assessing environmental responsibility practices within vocational institutions and for the certification and auditing processes to ensure continuous improvement. As part of the study, a case study was conducted on a Finnish secondary vocational institution, and the framework for the research was based on the environmental certification the institution is seeking from the nonprofit OKKA Foun-dation. The study’s data consisted of responses from a self-assessment provided by the vocational institution, which served as a basis for understanding the institution's current status. Addi-tionally, recent articles on environmental sustainability in educational institutions were reviewed to supplement the current state analysis and to offer better improvement sug-gestions for achieving the environmental certificate, providing a comprehensive view of environmental sustainability in educational institutions. A mixed-methods approach was chosen for the research, including data from the case institution and a literature review. The institution and individuals from the institution are not named to maintain anonymity. The institution has all the necessary capabilities to achieve the required certification level in the future. Many units have implemented sustainable practices, though differences exist among units, with some being more advanced in their practices than others. Differ-ences are found in practical methods and knowledge; unifying these practices is essential for the institution's success across all units. The institution's sustainability efforts face chal-lenges such as financial constraints, stakeholder diversity, and regional innovation barriers. The proposed development measures focus on strengthening community involvement and integrating sustainability into daily operations. Suggestions include improving procure-ment practices, increasing awareness, and actively engaging stakeholders. Additionally, emphasis was placed on internal communication and new procurement strategies to ad-dress cost challenges in sustainable product procurement. The study emphasizes that sustainable development is a continuous process that requires leadership commitment and strategic planning. Through OKKA certification, the institution can approach sustainability systematically by utilizing self-assessments, strategic planning, and stakeholder involvement. This helps establish a cohesive and evolving approach that supports environmental responsibility goals and enables broader societal impact.

Kestävä kehitys ja ympäristökestävyyden merkitys on lisääntynyt vuosien saatossa. Maail-manlaajuiset kuin kotimaiset säädökset, sekä hiilineutraalius tavoitteet asettavat myös opetusinstituutioille tarpeen kehittää heidän ympäristökestävyyttään. Tämän tutkimuksen tarkoituksena on muotoilla puitteet ammatillisten oppilaitosten ympäristövastuun käytän-töjen arvioinnille sekä sertifiointiprosessille ja auditoinnille jatkuvan parantamisen varmis-tamiseksi. Osana tutkielmaa on case-tutkimus suomalaisesta toisen asteen ammatillisesta oppitaloitoksesta ja tutkielman kehyksenä toimii oppilaitoksen hakema kestävän kehityk-sen sertifikaatti voittoa tavoittelemattomalta OKKA-järjestöltä. Tutkimusaineistona käytettiin ammattillisen oppilaitoksen tarjoamat vastaukset heidän itseiarviointiin, jonka perusteella lähdettiin rakentamaan käsitystä oppilaitoksen nykytilas-ta. Tämän lisäksi aineistona käytettiin opetusinstituutioiden ympäristökestävyydestä tehty-jä artikkeleita viime vuosilta täydentämään nykytila-analyysia sekä tarjoaamaan parempia parannusehdotuksia, jotta oppilaitos saavuttaa ympäristösertifikaatin ja tutkimus tarjoaa mahdollisimman laajan kuvan koulutuslaitoksien ympäristökestävyydestä. Tutkielman me-netelmäksi valikoitui sekamenetelmä, johon sisältyi case-yrityksen tarjoamat aineistot sekä kirjallisuuskatsaus. Tutkielman opetusinstituuttia ei mainita tai henkilöitä, jotka ovat osal-listuneet instituutiosta, jotta mahdollinen anonymeetti säilyy. Oppilaitoksella on kaikki mahdollisuudet saavuttaa tulevaisuudessa vaadittu sertifikaatin taso. Useissa yksiköissä on toteutettu kestäviä käytäntöjä, mutta yksiköiden välillä on eroa-vaisuuksia ja osa on edistyneempiä käytännöissään kuin toiset. Eroavaisuuksia löytyy käy-tännön menetelmissä sekä tiedossa, näiden toimintojen yhtenäistäminen on yksi keskei-nen osa instituution onnistumista jokaisessa yksikössä. Instituution kestävän kehityksen työ kohtaa haasteita, kuten taloudellisia rajoitteita, sidosryhmien moninaisuutta ja alueellisia innovaatiomuureja. Kehitysehdotukset keskittyvät yhteisön osallistamisen vahvistamiseen ja kestävyyden sisäl-lyttämiseen päivittäisiin toimintoihin. Ehdotuksia ovat muun muassa hankintakäytäntöjen parantaminen, tiedon lisääminen ja sidosryhmien aktiivinen mukaanotto. Lisäksi painotet-tiin sisäistä viestintää sekä uusia hankintastrategioita, joiden avulla kestävien tuotteiden kustannushaasteet voidaan ratkaista. Tutkimus korostaa, että kestävä kehitys on jatkuva prosessi, joka vaatii johdon sitoutumista ja strategista suunnittelua. OKKA-sertifioinnin kautta oppilaitos voi lähestyä kestävyyttä systemaattisesti, hyödyntäen itseisarviointeja, strategista suunnittelua ja sidosryhmien osallistamista. Tämä auttaa luomaan yhtenäisen ja kehittyvän toimintatavan, joka tukee ympäristövastuullisia tavoitteita ja mahdollistaa laajemman yhteiskunnallisen vaikuttami-sen.
Keywords: kestävä kehitys; arviointi; kehittäminen; ympäristövaikutukset; oppiminen; ympäristö; vocational institutions; educational institutions; auditing (evaluation); fi=Tuotantotalous (kauppatieteet)|en=Industrial Management|; Master's Programme in Industrial Management